Microencapsulation as a noble technique fro the application of bioactive compounds in the food industry: a comprehensive review - Mehta, Nitin; Kumar, Pavan; Verma, Akhilesh K.; Umaraw, Pramila; Kumar, Yogesh; Malav, Om Prakash; Sazili, Awis Qurni; Domínguez, Rubén; Lorenzo, José M. (MDPI AG, 2022)
The use of natural food ingredients has been increased in recent years due to the negative health implications of synthetic ingredients. Natural bioactive compounds are important for the development of health-oriented functional food products with better quality attributes. The natural bioactive compounds possess different types of bioactivities, e.g., antioxidative, antimicrobial, antihypertensive, and antiobesity activities. The most common method for the development of functional food is the fortification of these bioactive compounds during food product manufacturing. However, many of these natural bioactive compounds are heat-labile and less stable. Therefore, the industry and researchers proposed the microencapsulation of natural bioactive compounds, which may improve the stability of these compounds during processing and storage conditions. It may also help in controlling and sustaining the release of natural compounds in the food product matrices, thus, providing bioactivity for a longer duration. In this regard, several advanced techniques have been explored in recent years for microencapsulation of bioactive compounds, e.g., essential oils, healthy oils, phenolic compounds, flavonoids, flavoring compounds, enzymes, and vitamins. The efficiency of microencapsulation depends on various factors which are related to natural compounds, encapsulating materials, and encapsulation process. This review provides an in-depth discussion on recent advances in microencapsulation processes as well as their application in food systems.